TEACHING INFECTIOUS DISEASES THROUGH DISTANCE EDUCATION AND DIGITAL RESOURCES IN HIGHER MEDICAL EDUCATION DURING THE COVID-19 PANDEMIC (KIUT Publication, 2025)
The COVID-19 pandemic has had a significant impact on the global healthcare system and has also required new approaches in higher medical education. Traditional classroom-based learning has been replaced by distance education and digital resources. In particular, the role of modern technologies has become crucial in teaching subjects that require practical skills, such as infectious diseases.